2014
DOI: 10.1371/journal.ppat.1004415
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Nuclear Antigen 3A Promotes Cellular Proliferation by Repression of the Cyclin-Dependent Kinase Inhibitor p21WAF1/CIP1

Abstract: Latent infection by Epstein-Barr virus (EBV) is highly associated with the endemic form of Burkitt lymphoma (eBL), which typically limits expression of EBV proteins to EBNA-1 (Latency I). Interestingly, a subset of eBLs maintain a variant program of EBV latency - Wp-restricted latency (Wp-R) - that includes expression of the EBNA-3 proteins (3A, 3B and 3C), in addition to EBNA-1. In xenograft assays, Wp-R BL cell lines were notably more tumorigenic than their counterparts that maintain Latency I, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…We, and others, had previously shown that EBNA3A and EBNA3C can block transcription of two members of the INK4 CDKI family, p16 INK4a and p15 INK4b [ 12 , 30 , 32 , 78 ]. Furthermore it has been reported that these same two EBV proteins might also repress expression of a third member of the CIP/KIP family, p21 CIP1 [ 85 , 86 ]. Since intrinsic cell cycle inhibitors are emerging as important targets of EBNA3A and EBNA3C, we focused on the consequences of miR-221/miR-222 induction in LCLs.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, had previously shown that EBNA3A and EBNA3C can block transcription of two members of the INK4 CDKI family, p16 INK4a and p15 INK4b [ 12 , 30 , 32 , 78 ]. Furthermore it has been reported that these same two EBV proteins might also repress expression of a third member of the CIP/KIP family, p21 CIP1 [ 85 , 86 ]. Since intrinsic cell cycle inhibitors are emerging as important targets of EBNA3A and EBNA3C, we focused on the consequences of miR-221/miR-222 induction in LCLs.…”
Section: Discussionmentioning
confidence: 99%
“…In LCLs and Burkitt lymphoma tumor cells, the EBNA3 proteins have been shown to regulate distinct but extensively overlapping sets of cell genes (19)(20)(21)(22)(23)(24)(25)(26). EBNA3 proteins have been implicated in the pathogenesis of Burkitt lymphoma and in attenuating an antiproliferative DNA damage response during EBV transformation of primary B lymphocytes (19,(27)(28)(29). Moreover, EBNA3A and EBNA3C repression of the CDKN2A-encoded tumor suppressors p16 and p14 is essential for LCL growth, requires interaction with RBPJ, and is associated with increased H3K27me3 modification at the CDKN2A promoter (22,23,(30)(31)(32).…”
Section: Epstein-barr Virus (Ebv) Latent Gene Products Cause Human Camentioning
confidence: 99%
“…GSE59181). (29,30). EBNA3A initiates and maintains polycomb repressive signatures at the CXCL9 and CXCL10 loci (31), and EBNA3A expression in BL cells represses proapoptotic Bim expression (32).…”
Section: Arfmentioning
confidence: 99%